Competition Makes IT Better : Evidence on When Firms Use IT More Effectively - Iacovone, Leonardo (World Bank, Washington, DC, 2016)
This paper uses a unique firm-level data set for Mexico, with information never used for research before, to assess how use of information technology (IT henceforth) influences firm performance. Further, the paper explores if, in the context of increasing competition from China, this effect is different for firms more strongly affected by competition where incentives for upgrading and innovation may be more intense. In this perspective, the paper analyzes the complementarity between IT and other changes spurred by competition, taking advantage of the exogenous shock generated by Chinese competition. The results indicate that IT use has higher effects over productivity in the case of firms facing higher competition from China, in the domestic market and in the U.S. market. Furthermore, the paper shows how these changes appear to be driven by complementary investments in innovation and organizational changes.